Low temperature fabrication and characterization of Si-O-C cured alumina toughened zirconia (ATZ). (2017) - Markandan, Kalaimani; Chin, JitKai; Tan, Michelle T.T.
Abstract: Ceramics such as zirconia and alumina have witnessed wide research and engineering interest owing to their high specific strength, fracture toughness, elasticity, hardness and wear resistance. In this study, yttriastabilised zirconia (YSZ) reinforced alumina (Al2 O3 )were synthesized by gel casting and infiltrated with polymer derived ceramic (PDC) resin. The composite denoted as ATZ were characterized by means of SEM-based microstructural studies, X-ray diffraction (XRD) and Fourier Transform Infrared Spectrometry (FT-IR) studies. Microstructural characterization, composition profiles, XRD and FT-IR results reveal the formation of strong interfacial bonding of Al2 O3 microstructures within YSZ matrix. This suggests the effectiveness of dispersant used; Dolapix CE64 and the possibility of enhanced mechanical properties for the composite.